Chronic Periodontitis Genome-wide Association Study in the Hispanic Community Health Study / Study of Latinos. (January 2017) - Sanders, A.E.; Sofer, T.; Wong, Q.; Kerr, K.F.; Agler, C.; Shaffer, J.R.; Beck, J.D.; Offenbacher, S.; Salazar, C.R.; North, K.E.; Marazita, M.L.; Laurie, C.C.; et al.
Chronic periodontitis (CP) has a genetic component, particularly its severe forms. Evidence from genome-wide association studies (GWASs) has highlighted several potential novel loci. Here, the authors report the first GWAS of CP among a large community-based sample of Hispanics/Latinos. The authors interrogated a quantitative trait of CP (mean interproximal clinical attachment level determined by full-mouth periodontal examinations) among 10, 935 adult participants (mean age: 45 y, range: 18 to 76 y) from the Hispanic Community Health Study / Study of Latinos. Genotyping was done with a custom Illumina Omni2.5M array, and imputation to approximately 20 million single-nucleotide polymorphisms was based on the 1000 Genomes Project phase 1 reference panel. Analyses were based on linear mixed models adjusting for sex, age, study design features, ancestry, and kinship and employed a conventional P < 5 × 10 −8 statistical significance threshold. The authors identified a genome-wide significant association signal in the 1q42.2 locus ( TSNAX-DISC1 noncoding RNA, lead single-nucleotide polymorphism: rs149133391, minor allele [C] frequency = 0.01, P = 7.9 × 10 −9 ) and 4 more loci with suggestive evidence of association ( P < 5 × 10 −6 ): 1q22 (rs13373934), 5p15.33 (rs186066047), 6p22.3 (rs10456847), and 11p15.1 (rs75715012). We tested these loci for replication in independent samples of European-American ( n = 4, 402) and African-American ( n = 908) participants of the Atherosclerosis Risk in Communities study. There was no replication among the European Americans; however, the TSNAX-DISC1 locus replicated in the African-American sample (rs149133391, minor allele frequency = 0.02, P = 9.1 × 10 −3 ), while the 1q22 locus was directionally concordant and nominally significant (rs13373934, P = 4.0 × 10 −2 ). This discovery GWAS of interproximal clinical attachment level—a measure of lifetime periodontal tissue destruction—was conducted in a large, community-based sample of Hispanic/Latinos. It identified a genome-wide significant locus that was independently replicated in an African-American population. Identifying this genetic marker offers direction for interrogation in subsequent genomic and experimental studies of CP.